Troglitazone prevents mitochondrial alterations, β cell destruction, and diabetes in obese prediabetic rats - Higa, Moritake (The National Academy of Sciences, 1999)
To determine whether the antidiabetic action of troglitazone (TGZ), heretofore attributed to insulin sensitization, also involves protection of β cells from lipoapoptosis, we treated prediabetic Zucker Diabetic Fatty rats with 200 mg/kg per day of TGZ. Their plasma-free fatty acids and triacylglycerol fell to 1.3 mM and 111 mg/dl, respectively, compared with 2.0 mM and 560 mg/dl in untreated controls. Their islet triacylglycerol content was 34% below controls. In islets of control rats, β cells were reduced by 82% and the islet architecture was disrupted; β-cell glucose transporter-2 was absent, 85% of their mitochondria were altered, and they were unresponsive to glucose. In treated rats, the loss of β cells was prevented, as were the loss of β cell glucose transporter-2, the mitochondrial alterations, and the impairment of glucose-stimulated insulin secretion. We conclude that the antidiabetic effect of TGZ in prediabetic Zucker Diabetic Fatty rats involves prevention of lipotoxicity and lipoapoptosis of β cells, as well as improvement in insulin sensitivity.